Family Relationships at the Time of COVID-19: the Perspective of the Italian Sociological Review - Di Nicola, Paola (Italian Sociological Review, 2022)
The pandemic highlighted social processes that were unknown to many citizens. Not only did it reveal the high level of interdependency between nations and continents but also the marked disparity between the beneficiaries and victims of globalization. Some countries were provided with tangible proof of their underlying fragility, especially in terms of their economies and access to resources (such as vaccines). The gulf between rich and poor nations was also underlined, as well as domestic poverty gaps. Inequality and injustice emerged with all their tragic overtones. It is necessary to come to terms with, rather than cancel, the past in order to imagine a different future, also as far as the family is concerned. The analysis of the research data shows that Italian households adopted coping strategies during the lockdown. Financially speaking, they drew on their savings and reduced certain forms of consumption, while couples – above all women – tackled the emergency by buckling down to care work and family responsibilities. The social and relational repercussions of all this have yet to be fully considered. In light of these remarks, envisioning the future of the current and new generations becomes a high-stakes game. Pursuing the dynamics triggered by the pandemic will herald a return to the traditional family model with the wife-mother as homemaker or homeworker and the husband-father employed in flexible work with little security (meaning also a family with fewer financia